Low PKCa expression within the MRD-HR stratum defines a new subgroup of childhood T-ALL with very poor outcome - Milani, Gloria (Impact Journals LLC, 2014)
Pediatric T-cell Acute Lymphoblastic Leukemia (T-ALL) outcome has improved in the last decades, yet one patient in every four still relapses. Except treatment response and immunophenotype, few markers are reliably prognostic in pediatric T-ALL patients. Aiming to improve T-ALL risk stratification, we investigated a new candidate biomarker with potential prognostic relevance. A phosphoproteomic screening of 98 pediatric T-ALL samples at diagnosis had been performed using the high-throughput Reverse Phase Protein Arrays technique, which led to the identification of PKCαS657 as an activated protein with a broad variation among T-ALL samples. To evaluate PKCα potential as a prognostic biomarker, PKCα expression was analyzed using RQ-PCR in a cohort of 173 patients, representative of ALL2000-ALLR2006 AIEOP study. A threshold of PKCα expression with the highest discrimination for incidence of relapse was identified. Patients with PKCα down-regulation, compared to patients with PKCα levels above the threshold, presented a markedly increased cumulative incidence of relapse (43.8% vs. 10.9%, P<0.001), as well as a worse 4-year overall survival (66% vs. 87.9%, P=0.002) and event-free survival (53.1% vs. 85.2%, P=0.002). In particular, low PKCα expression identified cases with extremely poor outcome within the high-risk minimal residual disease (MRD) stratum, their incidence of relapse being of 69% vs. 15% in the high PKCα levels group. In a multivariate analysis adjusting for main prognostic features, PKCα proved to be an independent prognostic factor related to incidence of relapse. Very high risk patients within the high-risk MRD stratum, identified by PKCα expression, could be proposed for experimental therapeutic protocols.